A mobile toolkit and customised location server for the creation of cross-referencing location-based services - Ndakunda, Shange-Ishiwa Tangeni (Rhodes University, Faculty of Science, Department of Computer Science, 2013)
Although there are several Software Development kits and Application Programming Interfaces for client-side location-based services development, they mostly involve the creation of self-referencing location-based services. Self-referencing location-based services include services such as geocoding, reverse geocoding, route management and navigation which focus on satisfying the location-based requirements of a single mobile device. There is a lack of open-source Software Development Kits for the development of client-side location-based services that are cross-referencing. Cross-referencing location-based services are designed for the sharing of location information amongst different entities on a given network. This project was undertaken to assemble, through incremental prototyping, a client-side Java Micro Edition location-based services Software Development Kit and a Mobicents location server to aid mobile network operators and developers alike in the quick creation of the transport and privacy protection of cross-referencing location-based applications on Session Initiation Protocol bearer networks. The privacy of the location information is protected using geolocation policies. Developers do not need to have an understanding of Session Initiation Protocol event signaling specifications or of the XML Configuration Access Protocol to use the tools that we put together. The developed tools are later consolidated using two sample applications, the friend-finder and child-tracker services. Developer guidelines are also provided, to aid in using the provided tools.
Keywords: Location-based services -- Security measures; Mobile communication systems -- Security measures; Digital communications; Java (Computer program language); Application software -- Development -- Computer programs; User interfaces (Computer systems)